2016
DOI: 10.1186/s12877-016-0386-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of prevalence of sarcopenia by using a new bioelectrical impedance analysis in Chinese community-dwelling elderly people

Abstract: BackgroundThe aim of the present study was to validate the usefulness of the new octapolar multifrequency bioelectrical impedance analysis (BIA) for assessment of appendicular skeletal muscle mass (ASM) by comparing it with that of dual-energy X-ray absorptiometry (DXA) and to investigate the prevalence of sarcopenia in Chinese community-dwelling elderly according to Asian Working Group for Sarcopenia (AWGS) definition.MethodsA cross-sectional study was conducted in communities of Chengdu, China. A total of 94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 42 publications
4
77
2
1
Order By: Relevance
“…For patients with a walking speed of ≤0.8 m/s, we used the bioelectrical impedance analysis (BIA) to assess muscle mass. The results of BIA are very similar to those of double-energy X-ray absorptiometry and magnetic resonance imaging; BIA also offers the advantages of safety, technical simplicity, low cost, and high patient compliance (Wang et al, 2016;Chien, Huang & Wu, 2008). All the results of BIA have been standardized by using cross-validated Sergi.…”
Section: Methods Of Assessmentmentioning
confidence: 56%
“…For patients with a walking speed of ≤0.8 m/s, we used the bioelectrical impedance analysis (BIA) to assess muscle mass. The results of BIA are very similar to those of double-energy X-ray absorptiometry and magnetic resonance imaging; BIA also offers the advantages of safety, technical simplicity, low cost, and high patient compliance (Wang et al, 2016;Chien, Huang & Wu, 2008). All the results of BIA have been standardized by using cross-validated Sergi.…”
Section: Methods Of Assessmentmentioning
confidence: 56%
“…Skeletal muscle mass was quantified using Bioelectrical Impedance Analysis (BIA) (Model 1500; Bodystat, Isle of Man, UK). Although Dual-Energy X-ray Absorptiometry (DEXA) is commonly used for measuring appendicular lean mass index (ALMI) in sarcopenia studies 8,84 , BIA has been suggested as a valid and low-cost alternative for measuring Skeletal Muscle Mass Index (SMI) and is a common tool in larger population studies 27,85 . Indeed, a high correlation between muscle mass measured with BIA and DEXA has been reported 78,79 .…”
Section: Scientific Reports |mentioning
confidence: 99%
“…[6], hand grip strength was considered to be under 26 kg for males and 18 kg for females. After informing about the patient's dynamometer, they were allowed to try 3 times.…”
Section: Introductionmentioning
confidence: 99%